2018
DOI: 10.1071/cp17240
|View full text |Cite
|
Sign up to set email alerts
|

A cytological and molecular analysis of D-genome chromosome retention following F2–F6 generations of hexaploid×tetraploid wheat crosses

Abstract: Both hexaploid bread wheat (AABBDD) (Triticum aestivum L.) and tetraploid durum wheat (AABB) (T. turgidum spp. durum) are highly significant global food crops. Crossing these two wheats with different ploidy levels results in pentaploid (AABBD) F1 lines. This study investigated the differences in the retention of D chromosomes between different hexaploid × tetraploid crosses in subsequent generations by using molecular and cytological techniques. Significant differences (P < 0.05) were observed in the reten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…The gene(s) responsible for this trait has to be encoded by the A and/or B subgenomes, because no discernible difference was observed with respect to the three manifestations (above) between pentaploid wheats XE and TE which possess the same BBAA subgenomes (both are the BBAA component of hexaploid wheat TAA10) but with different sources of the D genomes, one being the original of TAA10 while the other being of A. tauschii , accession TQ18 ( Figure 1A ). Our results are consistent with an earlier observation that in segregating progenies of given pentaploid wheat, those individuals with more BBAA alleles from the hexaploid parent were trended to contain more D chromosomes than those with more alleles from the durum wheat ( Martin et al, 2011 ; Padmanaban et al, 2017a , 2018 ). However, because the pentaploid wheats constructed by these prior studies, being breeding oriented, are all with heterozygous BBAA genomes (hybrids between different genotypes of hexaploid wheat and durum wheat), other confounding factors, e.g., heterosis in the concerned trait, cannot be ruled out, and hence, an affirmative conclusion cannot be reached.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The gene(s) responsible for this trait has to be encoded by the A and/or B subgenomes, because no discernible difference was observed with respect to the three manifestations (above) between pentaploid wheats XE and TE which possess the same BBAA subgenomes (both are the BBAA component of hexaploid wheat TAA10) but with different sources of the D genomes, one being the original of TAA10 while the other being of A. tauschii , accession TQ18 ( Figure 1A ). Our results are consistent with an earlier observation that in segregating progenies of given pentaploid wheat, those individuals with more BBAA alleles from the hexaploid parent were trended to contain more D chromosomes than those with more alleles from the durum wheat ( Martin et al, 2011 ; Padmanaban et al, 2017a , 2018 ). However, because the pentaploid wheats constructed by these prior studies, being breeding oriented, are all with heterozygous BBAA genomes (hybrids between different genotypes of hexaploid wheat and durum wheat), other confounding factors, e.g., heterosis in the concerned trait, cannot be ruled out, and hence, an affirmative conclusion cannot be reached.…”
Section: Discussionsupporting
confidence: 93%
“…Nearly a century ago, the pioneering works by Sax and Kihara have independently demonstrated that hexaploid common wheat and tetraploid emmer wheat could be hybridized to produce fertile pentaploid hybrids (genome BBAAD) ( Sax, 1922 ; Kihara, 1925 ). Recent years have witnessed a renewed interest in the generation of pentaploid wheat for the purpose of reciprocally introgressing desirable traits from one species to the other (reviewed in Padmanaban et al, 2017b , 2018 ). Apart from the practical success ( Wang et al, 2005 ; Eberhard et al, 2010 ; Padmanaban et al, 2017a , b ), an interesting observation is that, in the progenies of pentaploid wheat, there exists a significant positive correlation between proportions of the hexaploid wheat BBAA genomic content and the retention of unbalanced D chromosome ( Martin et al, 2011 ; Padmanaban et al, 2017a ).…”
Section: Introductionmentioning
confidence: 99%
“…The recombination frequency is mainly affected by changes in the initiation of chromosome pairing, responses to the molecular control of chromosome pairing, and delayed or accelerated progression through the meiotic cell cycle stages ( Martinez-Perez et al, 2001 ; Pecinka et al, 2011 ; Pelé et al, 2017 ). Polyploids with odd-ploidy levels might lead to alien chromosomes remaining as univalents during homologous pairing in the meiotic metaphase ( Padmanaban et al, 2017 , 2018 ). As early as 1924, Kihara (1924) had already reported that the F 1 pentaploid wheat hybrids had 14 bivalents of AB chromosomes and seven univalents of D chromosomes.…”
Section: Discussionmentioning
confidence: 99%
“…In modern wheat breeding, the pentaploid-derived progenies could be used to introgressive useful agronomic traits into bread wheat cultivars, including high-yield potential and diseases resistance (leaf rust, stripe rust, powdery mildew) ( Reader and Miller, 1991 ; Leonova et al, 2002 ; Mohler et al, 2013 ; Xu et al, 2013 ; Yaniv et al, 2015 ; Simmonds et al, 2016 ). Moreover, the continuous selfing may result in nascent elite recombination and chromosome substitution or addition lines of hexaploid or tetraploid wheat, possibly after six or more generations, through the gain or loss of D chromosomes ( Padmanaban et al, 2018 ; Yang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%